Histomorphometric Analysis of Collagen and Elastic Fibres in the Cranial and Caudal Fold of the Porcine Glottis. (3rd July 2014) - Lang, A.; Koch, R.; Rohn, K.; Gasse, H.
Summary The porcine glottis differs from the human glottis in its cranial and caudal vocal folds (CraF, CauF). The fibre apparatus of these folds was studied histomorphometrically in adult minipigs. For object definition and quantification, the colour‐selection tools of the Adobe‐Photoshop program were used. Another key feature was the subdivision of the cross‐sections of the folds into proportional subunits. This allowed a statistical analysis irrespective of differences in thickness of the folds. Both folds had a distinct, dense subepithelial layer equivalent to the basement membrane zone in humans. The subsequent, loose layer was interpreted – in principle – as being equivalent to Reinke's space of the human vocal fold. The next two layers were not clearly separated. Due to this, the concept of a true vocal ligament did not appear applicable to neither CauF nor CraF. Instead, the body‐cover model was emphasized by our findings. The missing vocalis muscle in the CraF is substituted by large collagen fibre bundles in a proportional depth corresponding to the position of the muscle of the CauF. The distribution of elastic fibres made the CraF rather than the CauF more similar to the human vocal fold. We suggest that these data are useful for those wishing to use the porcine glottis as a model for studying oscillatory properties during phonation.